Structure and Content Analysis for Vocational High School Website in Indonesia. (March 2017) - Subagja, H; Abdullah, A G; Trisno, B; Nandiyanto, A B D
Abstract: Statistics about the condition of the school's website in Indonesia is still difficult. This study aims to determine website quality in terms of completeness of content's criteria of Vocational High School (VHS) in West Java, Indonesia. The method used is the content analysis and survey. Content analysis is reviewing the documents comprising the general category, while the survey is a observation process to get the facts from 272 school websites. Aspects of the structure and content of school website are including institutional information, educators and education personnel, curriculum, student, infrastructure, school achievement, and public access. The results of this study showed the average quality of the VHS website in West Java is still low. The recommendations are needed to improve the quality of the school website.